2013
DOI: 10.1155/2013/530946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical Treatment on Lipid Peroxidation Parameters and Antioxidant Status in the Serum of Patients with Peripheral Arterial Disease

Abstract: The various risk factors for peripheral arterial disease (PAD) are almost identical to those for atherosclerosis and include abnormal levels of lipids or lipoproteins. Lipid peroxidation parameters and total antioxidant capacity in the serum of male patients with PAD before surgery as well as 3–5 days and 7–10 days after surgery were measured. We also compared these parameters with those in a group of patients receiving simvastatin therapy. Concentrations of lipid hydroperoxides (LOOHs) and malondialdehyde, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Both parameters are lower in the case of alcoholism. The direct correlation between total antioxidant capacity (expressed as FRAP) and -SH group concentrations in the serum of patients was also reported [ 11 ]. Our study revealed that average concentration of thiols was 0.94 ±0.34 mmol/l ( p < 0.05) for patients with alcohol dependence, whereas it was 1.21 ±0.36 mmol/l ( p < 0.05) for healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…Both parameters are lower in the case of alcoholism. The direct correlation between total antioxidant capacity (expressed as FRAP) and -SH group concentrations in the serum of patients was also reported [ 11 ]. Our study revealed that average concentration of thiols was 0.94 ±0.34 mmol/l ( p < 0.05) for patients with alcohol dependence, whereas it was 1.21 ±0.36 mmol/l ( p < 0.05) for healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress will be produced when the balance between formation of free radicals in the body and the elements that remove them is broken, and this leads to ROS accumulation in tissue (Strzyzewski et al, ). It will result in functional tissue damage and cell death if ROS are not effectively neutralized by an antioxidant defense system (Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage to lipids and lipoproteins contributes to the development of atherosclerotic vascular diseases such as PAD. Previous studies report that this progression may be mitigated by paraoxonase (PON) antioxidant enzymes [12] [13] [14] through reduction in low-density lipoprotein oxidation [15]. For example, in a case study of 37 older people (mean age 69.9 ± 9 years) with PAD, PON1 genotype and PON1 activity were directly related to brachial flow-medicated vasodilation (p = 0.0004) [15].…”
Section: Introductionmentioning
confidence: 99%